2018
DOI: 10.1038/s41388-018-0617-1
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Src inhibition alters the BRAF-mutant tumor secretome to promote an invasive phenotype and therapeutic escape through a FAK>p130Cas>c-Jun signaling axis

Abstract: Few therapy options exist for patients with advanced papillary and anaplastic thyroid cancer. We and others have previously identified c-Src as a key mediator of thyroid cancer pro-tumorigenic processes and a promising therapeutic target for thyroid cancer. To increase the efficacy of targeting Src in the clinic, we sought to define mechanisms of resistance to the Src inhibitor, dasatinib, to identify key pathways to target in combination. Using a panel of thyroid cancer cell lines expressing clinically releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…Experimental and epidemiological studies revealed that chronic inflammation is a feature of ATC [44,45,46]. In particular, ATC shows increased expression of several proinflammatory cytokines (especially of IL-1β) that, via a feedforward autocrine loop, promotes cell invasion in this cancer type [46]. In order to also verify the physiological relevance of IL-1β in our in vitro cell models, we firstly investigated IL-1β secretion and signaling in ATC CAL62 and 8505C cells as well as in PTC B-CPAP and TPC1 cells for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental and epidemiological studies revealed that chronic inflammation is a feature of ATC [44,45,46]. In particular, ATC shows increased expression of several proinflammatory cytokines (especially of IL-1β) that, via a feedforward autocrine loop, promotes cell invasion in this cancer type [46]. In order to also verify the physiological relevance of IL-1β in our in vitro cell models, we firstly investigated IL-1β secretion and signaling in ATC CAL62 and 8505C cells as well as in PTC B-CPAP and TPC1 cells for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we identified a novel mechanism in TGF-β1 signaling [43]. FAK is a critical substrate that regulates several cellular events including migration and invasion through its dual function as a kinase and scaffolding protein [46]. FAK autophosphorylation leads to the recruitment of Src, and this complex signals to downstream effectors, including pro-invasive genes, such as MMPs [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POLR2A was pulled down by BCAR1 in 293T cells, probably due to tissue-specific or tumor-specific interactions between these two proteins. However, the BCAR1/c-JUN cascade has been shown to upregulate the expression of BRAF, 40 which is believed to be an upstream regulator of POLR2A. 41 Based on these findings, we speculate that BCAR1 can, at the very least, indirectly upregulate POLR2A expression, which has critical biological functions leading to cell proliferation, cell growth, and subsequent poor prognosis in lung cancer cases (Fig 4).…”
Section: Discussionmentioning
confidence: 92%
“…Autoinducers and their receptors are important targets for disrupting pathogenic processes and an active area of research (74). The corollary in cancer is the secretion of factors by therapeutically stressed tumor cells or the microenvironment that can support tumor cell survival (75)(76)(77).…”
Section: Insights From Single-cell Organisms and Hematologic Malignanmentioning
confidence: 99%